NEED ANALYSIS OF LEARNING MATERIALS FOR GEADE TEN STUDENTS OF CULINARY ART STUDY PROGRAM AT SMK - Deni Melyati (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
English learning materials at Vocational high school or SMK can be seen as an exposure to the use of the language which will help the students in achieving the higher proficiency of English. Unfortunately, materials which are relevant or even appropriate to the needs of the students of SMK were limited. Although materials take an important part in the processes of teaching and learning, to select and to find a good resource of materials was not an easy work. Teachers should consider several things before choosing and giving it to the students. Whatever materials will be chosen, it is really important to consider the condition and the capacity of the students, and the materials should meet with students’ particular needs and interest. Because, it helping them in achieving the goals, especially for vocational high school. To know the learning materials that students need, the researcher use ESP course design. ESP course design usually includes a stage in which the course developers identify what specific language and skills the group of language learners will need. The identification of language and skills is used in determining and refining the content for the ESP course. It can also be used to assess learners and learning at the end of the course. This process is termed ‘needs analyses. The aim of the research was to describe the learning materials needed by the ten grade students culinary art study program SMKN 3 Sungai Penuh. The finding of the research was the information what students’ English learning materials needed.